Mutagenicity Activity of Jatropha Curcas L. (Euphorbiaceae) Latex - I.Kristiani, Fazwishni Siregar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Folklore uses of Jatropha curcas L. latex are to cure toothache, as a mouth rinse to treat bleeding gums, as a hemostatic and a wound dressing and many others. Even though the latex has been used traditionally as a plant medicament, scientific investigation including toxicological studies was very limitedObjective: The purpose of this study was to evaluate the mutagenicity of J. curcas latex by Ames method. Materials and Methods: Five increasing concentrations of diluted latex (312-5000 !-tg) were mixed with phosphate buffer or 59 mix and cultured bacteria, incubated, and then added to top agar solution. The mixture was poured into a Petri dish on top of minimal glucose agar. After incubation for 2 days, the reverted coloni were counted. If the number of revertant increases with the dose and the number are more then twice as many as that of spontaneous revertant per plate, the compound should be judged to be positive.Result: Results showed that there were no increased numbers of colonies treated with increasing concentration of J. curcas latex. This finding is observed in all bacteria used. Conclusion: J. curcas latex is not mutagenic assessed by Ames method.Key words: Jatropha curcas latex, mutagenicity test, Ames test, traditional medicament, toxicology.